PENERAPAN EVIDENCE BASED NURSING DENGAN INTERVENSI TERAPI MUSIK KLASIK INSTRUMENTAL DALAM MENINGKATKAN GCS PADA PASIEN STROKE DISERTAI PENURUNAN KESADARAN DI RUANG INTENSIVE CARE UNIT RSUD TARAKAN - Siva Herawati (2022)
Stroke is a cerebrovascular disease or blood vessel in the brain characterized by damage or death of brain tissue due to reduced or blocked blood and oxygen flow to the brain, resulting in impaired brain function. Sensory stimulation is a way to improve consciousness and development in comatose patients. Sensory stimulation that has a major influence in increasing awareness is auditory stimulation, auditory stimulation is given in the form of music therapy. Stimulation of listening to music can affect the level of consciousness both physically, mentally, religiously and socially. The effect of giving music therapy is a decrease in adrenaline activity, a decrease in neuromuscular tension, and an increase in the threshold of consciousness. This study aims to determine the results of the application of evidence based nursing with instrumental classical music therapy intervention to increase the Glassgow Coma Scale (GCS) in stroke patients in the Intensive Care Unit. The assessment in this study used the Glassgow Coma Scale (GCS) value to assess the patient's level of consciousness. The results showed that after 3 days of classical instrumental music therapy, it had an effect on increasing GCS in stroke patients with decreased consciousness in the Intensive Care Unit of RSUD Tarakan.